Grade repetition in Secondary Education in an organizational perspective - González Tapia, Javier; Alvarez Alvarez, Carmen (Avances en Supervisión Educativa, 2022)
With the entry into force of the LOMLOE, new legislation has been approved to regulate the promotion and evaluation of students in Secondary Education in Spain, introducing important changes in the criteria for repetition. In this paper, we present the most important findings of the academic literature in terms of non-promotion, highlighting the empirical evidence and alternatives, as well as aspects related to school management. In addition, the present study has been carried out by means of an open questionnaire to directors of Secondary Education centers in a community and by conducting semi-structured interviews with inspectors of the Department of Education, in order to evaluate the status and effects of school repetition in the region on the student body. The qualitative results obtained show a gradual withdrawal of this measure by the schools, mainly due to the change in legislation and mentality, now more oriented towards competency-based education.